Food Allergies and Sensitivities: Current Research and Future Directions (International Journal of Food and Nutritional Sciences, 2022)
Food allergies and sensitivities represent complex and dynamic areas of study, characterized by distinct immunological and non-immunological responses to specific dietary elements. This review explores the current landscape and future directions in research, diagnostics, and management of these conditions. A nuanced understanding of allergies, rooted in hypersensitive immune reactions to specific proteins, is paralleled by insights into sensitivities, which involve varied non-immunological responses. Ongoing and future research focuses on precision medicine, leveraging genomics for individualized treatment approaches. Immunotherapy innovations seek to enhance desensitization strategies, while microbiome research sheds light on the role of gut bacteria in shaping immune responses. Biomarker discovery, digital health solutions, and allergen-free food development contribute to comprehensive care. The exploration of epigenetics and environmental influences expands the horizon of causative factors. The holistic approach emphasizes patient education, advocacy, and interdisciplinary collaboration. As the field advances, the overarching goal is to improve the quality of life for individuals affected by these conditions, embracing technological innovations and fostering collaborative efforts in pursuit of personalized and precise management strategies